2018
DOI: 10.3390/polym10070733
|View full text |Cite
|
Sign up to set email alerts
|

Negatively Charged Porous Thin Film from ABA Triblock Copolymer Assembly

Abstract: The preparation of well-arranged nano-porous thin films from an ABA triblock copolymer of polystyrene- block -poly(sodium 4-styrenesulfonate)- block -polystyrene (PS-PNaSS-PS) is reported. This copolymer was self-assembled in a N , N -dimethylformamide (DMF)/water mixture and the resulting micellar solution was used to prepare thin films via the compact packing of the flower-like micelles using spin coating method. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This shows that the electrostatic repulsion of Mg 2+ by the membrane was much higher than that of Na + , hence why the high rejection of MgCl 2 was observed. It can be concluded that the composite membranes in this study possess negatively charge surfaces due to the AlO 4 tetrahedra interactions with the SiOH of ZSM-22 nanoadditives [ 84 , 86 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that the electrostatic repulsion of Mg 2+ by the membrane was much higher than that of Na + , hence why the high rejection of MgCl 2 was observed. It can be concluded that the composite membranes in this study possess negatively charge surfaces due to the AlO 4 tetrahedra interactions with the SiOH of ZSM-22 nanoadditives [ 84 , 86 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…This assessment led to cheaper water softening applications using lower applied pressure (<1 bar) in the NF or RO membrane systems. The interaction of these solutes with the composite membrane matrix containing negatively charge nanoadditives, as opposed to size exclusion, was also a possible mode for membrane rejection [84,85]. The relatively high charge on divalent Mg ion means it is strongly attracted to the negatively charged membrane surface than the monovalent Na ion, resulting in the different observed rejection profiles.…”
Section: Flux and Rejection Analysismentioning
confidence: 99%
“…Their systematic study, investigated the effect of solvent mixtures, solvent mixture ratios, molecular weights, block ratios, and polymer concentration. [ 245–247 ] It was shown that independent of the block ratios aggregates of different morphologies could be prepared depending on the solvent mixture ratios (THF/H 2 O). At constant polymer concentrations, different type of morphologies could be prepared (spheres, short worms, and vesicles).…”
Section: Novel Applications Of Raftmentioning
confidence: 99%
“…[ 245,246 ] They also demonstrated that when the block ratios were even (PS 5k ‐PNaSS 5k ‐PS 5k , PS 10k ‐PNaSS 10k ‐PS 10k ) depending on the choice of organic solvent (THF or DMF) hydrophobic LCVs or hydrophilic spheres could be prepared. [ 246,247 ] All these colloidaly stable aggregates were used to make porous thin film membranes on a solid support via spin‐coating. Image analysis and filtration tests suggested that the pore size of these porous thin films were in the range of 10–30 nm making these membranes suitable for ultrafiltration.…”
Section: Novel Applications Of Raftmentioning
confidence: 99%
“…Nanoporous thin films are widely used for various applications such as energy conversion and storage [ 1 , 2 , 3 , 4 ], the selective separation of molecules [ 5 , 6 , 7 ] and filtration [ 8 , 9 , 10 ]. Commercially available nanoporous membranes generally exhibit broad size distributions and relatively large thickness.…”
Section: Introductionmentioning
confidence: 99%